Generation of a gene-corrected human iPSC line (CSUASOi004-A-1) from a retinitis pigmentosa patient with heterozygous c.2699 G>A mutation in the PRPF6 gene - Yuqin Liang; Xihao Sun; Chunwen Duan; Yalan Zhou; Zekai Cui; Chengcheng Ding; Jianing Gu; Shengru Mao; Shangli Ji; Hon Fai Chan; Shibo Tang; Jiansu Chen (Stem Cell Research, 2022)
Retinitis pigmentosa (RP) is one of the most common inherited retinal diseases characterized by nyctalopia, progressive vision loss and visual field contraction. we previously generated an induced pluripotent stem cell line (CSUASOi004-A) from a RP patient with heterozygous PRPF6 c.2699 G>A (p.R900H) mutation. Here we corrected the PRPF6 c.2699 G>A mutation genetically using CRISPR/Cas9 technology to generate an isogenic control (CSUASOi004-A-1), which can provide a valuable resource in the research of the disease.